Bacteroides gracilis, an important anaerobic bacterial pathogen. - Johnson, C C (1985)
Clinical isolates of agar-pitting, formate-fumarate-requiring, anaerobic gram-negative bacilli were recharacterized in consideration of the species descriptions of Bacteroides ureolyticus and the newly described B. gracilis, Campylobacter concisus, and Wolinella sp. During an 11-year period, 7.5% (101 of 1,341) of all specimens yielding anaerobes were found to contain an organism in this group. Of the 71 isolates that were available for study, 43 were B. ureolyticus, 23 were B. gracilis, and 5 were in the Wolinella-C. concisus group. The role in infection and patterns of antimicrobial susceptibility for B. ureolyticus and B. gracilis were studied. Review of the clinical data indicated that 83% of B. gracilis strains were recovered from patients with serious visceral or head and neck infection, whereas 73% of B. ureolyticus isolates were recovered from superficial soft-tissue or bone infections. The strains of B. ureolyticus were uniformly susceptible to the tested antimicrobial agents. B. gracilis, however, showed some striking resistance, with penicillin active against only 67% and the cephalosporins active against 67 to 84% of the isolates tested. The association of B. gracilis with serious deep-tissue infection, coupled with the relatively high frequency of antibiotic resistance, indicates that it is an important, previously unrecognized, pathogen.